Anoplophora rnalasiaca Thomson (Coleoptera Cerambycidae Lamiinae Lamiini) in Europe (Bollettino di zoologia agraria e bachicoltura, 2024)
Anoplophora malasiaca Thomson is recorded for the first time in ltaly.It is a xilophagous species present in Japan, Korea and Taiwan. lt's a quarantine pest for Europe.
Keywords: Anoplophora malasiaca; Anoplophorawhite-spotted longicom beetle; xilophagous; nursery; Italy; Europe